Large coverage black‐bright blood interleaved imaging sequence (LaBBI) for 3D dynamic contrast‐enhanced MRI of vessel wall. Issue 3 (19th June 2017) - Qi, Haikun; Huang, Feng; Zhou, Zechen; Koken, Peter; Balu, Niranjan; Zhang, Bida; Yuan, Chun; Chen, Huijun
Abstract : Purpose: To propose a large coverage black‐bright blood interleaved imaging sequence (LaBBI) for 3D dynamic contrast‐enhanced MRI (DCE‐MRI) of the vessel wall. Methods: LaBBI consists of a 3D black‐blood stack‐of‐stars golden angle radial acquisition with high spatial resolution for vessel wall imaging and a 2D bright‐blood Cartesian acquisition with high temporal resolution for arterial input function estimation. The two acquisitions were performed in an interleaved fashion within a single scan. Simulations, phantom experiments, and in vivo tests in three patients were performed to investigate the feasibility and performance of the proposed LaBBI. Results: In simulation tests, the estimated K trans and v p by LaBBI were more accurate than conventional bright‐blood DCE‐MRI with lower root mean square error in all the tested conditions. In phantom test, no signal interference was found on the 2D scan in LaBBI. Pharmacokinetic analysis of the patients' data acquired by LaBBI showed that K trans was higher in fibrous tissue (0.0717 ± 0.0279 min −1 ), while lower in necrotic core (0.0206 ± 0.0040 min −1 ) and intraplaque hemorrhage (0.0078 ± 0.0007 min −1 ), compared with normal vessel wall (0.0273 ± 0.0052 min −1 ). Conclusion: The proposed LaBBI sequence, with high spatial and temporal resolution, and large coverage blood suppression, was promising to probe the perfusion properties of vessel wall lesions. Magn Reson Med 79:1334–1344, 2018. © 2017 International Society for Magnetic Resonance in Medicine.